47.2k views
5 votes
The polynomial f(x) leaves a remainder of - 3 and - 7 when divided by (3x - 1) and (x +1) respectively.

Find the remainder when f(x) is divided by (3x^2 + 2x -1).


User Franek
by
5.4k points

1 Answer

3 votes

Explanation:

Here, f(x) is the given polynomial.

By remainder Theorem,

When divided by (3x-1),

f(1/3) = -3........(1)

When divided by (x+1),

f(-1) = -7.........(2)

Another polynomial is 3x²+2x-1

Solving,

3x²+2x-1

= 3x²+3x-x-1

=3x(x+1)-(x+1)

=(3x-1)(x+1)

So

f(x) = (3x-1)(x+1)Qx + (ax+b)

For f(-1),

-7 = -a+b

b= a-7

For f(1/3),

-3 = a/3+b

or, -3 = a/3+a-7

or, 4×3 = 4a

or a = 3

Also, b = 3-7 =-4

Hence, remainder is (3x-4)

User OzdrgnaDiies
by
4.8k points